2022
DOI: 10.1371/journal.pone.0271248
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory phosphoproteomics profiling of Aedes aegypti Malpighian tubules during blood meal processing reveals dramatic transition in function

Abstract: Malpighian tubules, the renal organs of mosquitoes, facilitate the rapid dehydration of blood meals through aquaporin-mediated osmosis. We performed phosphoproteomics analysis of three Malpighian tubule protein-libraries (1000 tubules/sample) from unfed female mosquitoes as well as one and 24 hours after a blood meal. We identified 4663 putative phosphorylation sites in 1955 different proteins. Our exploratory dataset reveals blood meal-induced changes in phosphorylation patterns in many subunits of V-ATPase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Specifically, AaAQP1 was detected on the apical membrane of the ileum and in the apical membrane of the rectal pads ( Figure 1 ) where it could play a role in absorbing water from the gut contents prior to excretion. In particular, the strong immunoreactive staining on the apical membrane of rectal pads 24hr PBM fits with the implied increased absorptive activities during this time ( 23 , 52 ). AaAQP2 was detected in the ileum at 0.5hr PBM but, we could not verify if AaAQP2 was in the rectal pads because we did not have sections of rectal pads for NBF or 0.5hr PBM.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Specifically, AaAQP1 was detected on the apical membrane of the ileum and in the apical membrane of the rectal pads ( Figure 1 ) where it could play a role in absorbing water from the gut contents prior to excretion. In particular, the strong immunoreactive staining on the apical membrane of rectal pads 24hr PBM fits with the implied increased absorptive activities during this time ( 23 , 52 ). AaAQP2 was detected in the ileum at 0.5hr PBM but, we could not verify if AaAQP2 was in the rectal pads because we did not have sections of rectal pads for NBF or 0.5hr PBM.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study by Kandel and colleagues examined AQP regulation in Ae. aegypti by phosphorylation and concluded that it is more likely that AQPs are regulated by membrane translocation during the post-blood feeding period in adult female mosquitoes ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, salt stress induction of H + ATPase expression has only been documented in salt-tolerant plants where this stress induces V-type and P-type H + ATPase expression in key tissues involved in sequestering or eliminating excess Na + 35 . Forms of post-translational regulation of VHA function have been noted in animals that involve the association or dissociation of V 0 and V 1 complexes as means to stimulate or inhibit activity respectively following an acute challenge 36 , 37 . For example, serotonin regulates VHA assembly leading to enhanced activity as described in Calliphora salivary glands 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Bradley and Phillips 10 , however, found that application of serotonin, cAMP, and theophylline to in vitro preparations of A. taeniorhynchus posterior recta did not impact trans-rectal potential difference or secretion rate. More recently, using phosphoproteomics, Kandel et al 37 showed that the degree of VHA subunit phosphorylation in the Malpighian tubules of adult female Aedes aegypti did not differ between unfed and 1 h post blood meal when VHA activity is high and driving rapid urine production. Instead, VHA subunits are dephosphorylated 24 h post blood meal paralleling the reduction in ion and water transport in this organ.…”
Section: Figurementioning
confidence: 99%